Analysis of the Effect of Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Impirical Study at Sanggar Senam Mutiara, Semarang City) - Lasmiatun, KMT; Nabila Wijaya (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to analyze and prove the influence of Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable at Sanggar Senam Mutiara in the city of Semarang. The method used is quantitative. With the research results, service quality and customer satisfaction have a significant positive effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction. And customer satisfaction is able to mediate the relationship between the influence of service quality variables on customer loyalty